Monoclonal antibodies targeting the influenza virus N6 neuraminidase - Strohmeier, Shirin; Amanat, Fatima; Carreño, Juan Manuel; Krammer, Florian (Frontiers in Immunology, 2022)
Influenza A viruses are a diverse species that include 16 hemagglutinin (HA) subtypes and 9 neuraminidase (NA) subtypes. While the antigenicity of many HA subtypes is reasonably well studied, less is known about NA antigenicity, especially when it comes to non-human subtypes that only circulate in animal reservoirs. The N6 NA subtypes are mostly found in viruses infecting birds. However, they have also been identified in viruses that infect mammals, such as swine and seals. More recently, highly pathogenic H5N6 subtype viruses have caused rare infections and mortality in humans. Here, we generated murine mAbs to the N6 NA, characterized their breadth and antiviral properties in vitro and in vivo and mapped their epitopes by generating escape mutant viruses. We found that the antibodies had broad reactivity across the American and Eurasian N6 lineages, but relatively little binding to the H5N6 NA. Several of the antibodies exhibited strong NA inhibition activity and some also showed activity in the antibody dependent cellular cytotoxicity reporter assay and neutralization assay. In addition, we generated escape mutant viruses for six monoclonal antibodies and found mutations on the lateral ridge of the NA. Lastly, we observed variable protection in H4N6 mouse challenge models when the antibodies were given prophylactically.